KEJADIAN INFEKSI HEPATITIS B PADA BAYI DAN ANAK YANG DILAHIRKAN OLEH IBU DENGAN HBSAG POSITIF DI KABUPATEN MAGELANG JAWA TENGAH TAHUN 2014-2016 - Nasir Ahmad; Hari Kusnanto (Berita Kedokteran Masyarakat (BKM), 2017)
PurposeThis study aimed to examine the prevalence rate of Hepatitis B Virus (HBV) infection in infants aged more than 9 months born to HbsAg-positive mothers as well as the distribution of the cases in Magelang Regency for the years 2014-2016.Method The study used a survey approach with total sampling. The sample of this research consisted of infants aged more than 9 months born to HBsAG-positive mothers diagnosed from laboratory examination (Rapid Diagnostic Test) based on the report from the Health Office of Magelang Regency for the years 2014-2016. The method of analysis used was descriptive. The HBsAg of the sample was examined using HBsAg Rapid Test Cassette and confirmed using Enzyme-Linked Fluorescence Assay (ELFA) methods at a laboratory.Results The prevalence rate of Hepatitis B virus infection in infants born to HBsAG-positive mothers in Magelang Regency was 0 percent (0/61). The history of the administration of HB0 vaccine <12 hours to respondents reached 100 percent and the history of the administration of HBIg <12 hours was 68.85 percent. The history of respondents’ caesarean delivery was 37.7 percent. The history of therapy of respondents was by giving curcuma and Java ginger (temulawak). The price of HBIg is relatively expensive Rp. 1,000,000 – Rp. 4,999,999.ConclusionThis study concludes that there was no vertical transmission with 100 percent history of the administration of HB0 vaccine.